# |
ODE |
Mathematica |
Maple |
\[
{}x^{\prime \prime }+x+x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x^{\prime }+x-x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+x^{\prime }+x+x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime } = \left (2 \cos \left (x\right )-1\right ) \sin \left (x\right )
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime }-{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime \prime } = 8 x^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = 4 x \sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = -{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = {y^{\prime }}^{2}-y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-{y^{\prime }}^{2} = 6 x^{5}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (-3+y\right ) y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}3 y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right ) y^{\prime \prime }+\cos \left (y\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime \prime }+y^{\prime \prime }+2 y {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 4 x \sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = {y^{\prime }}^{2}-y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (-3+y\right ) y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime } \left (y^{\prime }-2\right )
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } y^{\prime \prime } = {y^{\prime }}^{2}-1
\] |
✓ |
✓ |
|
\[
{}3 y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+2 {y^{\prime }}^{2} = 3 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -y^{\prime } {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+4 y = y^{3}
\] |
✗ |
✗ |
|
\[
{}\left (1+y\right ) y^{\prime \prime } = {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime } = -3 x {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime \prime }}^{2}+2 y = 2 x
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+2 \sin \left (x\right ) = \sin \left (2 t \right )
\] |
✗ |
✗ |
|
\[
{}{y^{\prime \prime }}^{2}-5 y^{\prime \prime } y^{\prime }+4 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}-2 y^{\prime \prime } y^{\prime }+y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}2 y y^{\prime \prime }+y^{2} = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}t \left (y y^{\prime \prime }+{y^{\prime }}^{2}\right )+y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } = \frac {y^{\prime }}{x}+\frac {x^{2}}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sqrt {1-{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sqrt {1+y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime } \ln \left (y^{\prime }\right )
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime } \left (1+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}3 y^{\prime \prime } y^{\prime } = 2 y
\] |
✗ |
✓ |
|
\[
{}2 y^{\prime \prime } = 3 y^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{3} y^{\prime \prime } = -1
\] |
✓ |
✗ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime } y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {\mathrm e}^{2 y}
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime }-3 {y^{\prime }}^{2} = 4 y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+{x^{\prime }}^{2}+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-2 {x^{\prime }}^{2}+x^{\prime }-2 x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }-x \,{\mathrm e}^{x^{\prime }} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+{\mathrm e}^{-x^{\prime }}-x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+x {x^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\left (x+2\right ) x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-x^{\prime }+x-x^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y+y^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\mu \left (1-y^{2}\right ) y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-\frac {t}{y} = \frac {1}{\pi }
\] |
✓ |
✗ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y+\frac {y^{3}}{5} = \cos \left (w t \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{5}+y+\frac {y^{3}}{5} = \cos \left (w t \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = \frac {1}{\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}2 \left (2 a -y\right ) y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = y^{2} \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime \prime }+x {y^{\prime }}^{2}-y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}n \,x^{3} y^{\prime \prime } = \left (-x y^{\prime }+y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (x^{2} y^{\prime \prime }-x y^{\prime }+y\right ) = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{2} y^{\prime \prime }-3 y^{2} y^{\prime } x +4 y^{3}+x^{6} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime }-x^{2} y y^{\prime }-x y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}x \left (x^{2} y^{\prime }+2 x y\right ) y^{\prime \prime }+4 x {y^{\prime }}^{2}+8 x y y^{\prime }+4 y^{2}-1 = 0
\] |
✗ |
✗ |
|
\[
{}x \left (x y+1\right ) y^{\prime \prime }+x^{2} {y^{\prime }}^{2}+\left (4 x y+2\right ) y^{\prime }+y^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2}-{y^{\prime }}^{4} = 0
\] |
✓ |
✓ |
|
\[
{}a^{2} y^{\prime \prime } = 2 x \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✗ |
|
\[
{}x^{2} y y^{\prime \prime }+x^{2} {y^{\prime }}^{2}-5 x y y^{\prime } = 4 y^{2}
\] |
✓ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|